Risks of mental problems among medical students in a public university in Malaysia - Minhat, Halimatus Sakdiah; Abdalrheem, Tasneem Abdalgfar Alawad (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2019)
Introduction: Mental problems have become increasingly important public health issue globally. This study aimed to determine the prevalence and factors associated with depression, anxiety, and stress among medical students in a public university in Malaysia. Methods: A total of 447 medical students were sampled by stratified proportion-ate to size sampling according to year of study. Validated self-administered questionnaire was used consisted of 5 sections namely, socio-demographic factors, social support received from family members and friends, presence of co-morbidity, previous history of resolved mental problem and Depression Anxiety Stress Scale DASS- 21. Data was analysed by using the statistical computer software ‘Statistical Package for Social Science (SPSS)’ version 22 involving three levels of analysis (descriptive, chi square and multiple logistic regression). Results: Only 31.1% of the respondents were found to be depressed with mainly within the moderately depressed category, 53.9% had anxiety and 26% were having stress. Perceived social support received from family members was a significant predicting factor for depression, anxiety and stress. Conclusion: High proportion of depression, anxiety and level of stress among medical students were found. The stressful medical program is putting medical students at risk of mental problems. Parents and family members should be encouraged to be more involved in any related programs to promote better mental health and well-being of medical students.